Radiography and ultrasound of the equine neck. (2nd July 2021) - Dixon, Jonathon J; Meehan, Lucy
Abstract : Diagnostic imaging of the equine neck is undertaken for a wide variety of conditions. In many cases, radiography is the principal imaging modality, often complemented by ultrasound examination. Common conditions encountered include osteoarthritis, articular process joint osteochondral fragmentation, cervical vertebral malformation ('wobbler'), fractures and numerous soft tissue lesions. The complex three-dimensional anatomy of the region limits interpretation of planar images and, in some cases, cross-sectional imaging (such as computed tomography) may be required. However, careful use of radiography and ultrasound can help clinicians to achieve a diagnosis in many cases, often from combining conventional and lesion-orientated projections with a thorough clinical examination.